Effects of ammonium sulfate [(NH4)2SO4] and urea (CH4N2O) n sago hampas hydrolysate (SHH) for bioethanol production - Dayang Nurfaizatulqurain, Abang Zaidel (Universiti Malaysia Sarawak (UNIMAS), 2016)
Production of bioethanol from lignocellulosic biomass piques the interest of many scientists due to the depleting crude oil supplies and the land competition of food versus fuel due to the production of bioethanol from food crops such as corns and sugar canes. Sago hampas, which can be found abudantaly in Malaysia, has been proven to be able to produce bioethanol. Nitrogen sources are important in bioethanol production whereby adequate amount is able to boost yeast growth and producing higher amount of bioethanol in shorter time. Researches have been conducted and it was found that yeast extract and peptone yield the highest amount of bioethanol. However, they are expensive. Hence in this study, the effects of ammonium sulfate (1.8 g/L) and urea (0.8 g/L) on the bioethanol yield and glucose consumption is analysed in order to determine which nitrogen souce can best replace yeast extract and peptone in low-cost productionof bioethanol.